Discriminant Function Analysis to Distinguish the Performance of Information and Communication Technology (ICT) Companies (A Study of U.S. Companies Listed in U.S. Stock Market) - Soekarno, Subiakto; Kinanthi, Enggar Sukma (School of Business and Management Institut Teknologi Bandung, 2020)
Abstract. The growing important role of ICT companies in digital era has attracted many institutions and researchers to conduct studies to measure the value creation created by digitalization. However, not many of them emphasize the importance of financial information as a performance measurement for ICT companies that are useful for their sustainability in the rapid pace of technology. Therefore, this study aims to find the importance of financial ratios in assessing the performance of ICT companies. This study uses discriminant function analysis to find the best financial ratios that distinguish the ICT companiesâ€™ performance based on their grade in the credit ratings. The scope of this study is 70 US-based companies listed in US stock market within ICT groups with 35 companies in each group of Investment Grade and Non-investment Grade. There are 4 financial ratios that best discriminate the performance between the two groups which are ROA, CFO to current liabilities, total debt to EBITDA, and CFO to net sales. This model has a predictive accuracy or early warning ability of 87.1% in the latest full-year financial statements prior to rating date and 80% in the longer period (up to 3rd last full-year financial statements prior to rating date).Keywords:Â Discriminant function analysis, financial ratio, performance, information and communication technology